The Influence of Financial and Non-Financial Characteristics on the Quality of Sustainability Disclosure of Manufacturing Companies in Indonesia (E-Jurnal Akuntansi, 2024)
Company transparency related to commitment to achieving SDGs as well as environmental and social impacts is conveyed through sustainable transmission (sustainability disclosure). This research aims to empirically analyze the influence of financial characteristics (profitability and leverage) and non-financial characteristics (gender, age, educational background, tenure of the President Director and citizenship) on the quality of disclosure of manufacturing companies in Indonesia. The research uses panel data regression analysis techniques with the Eviews 12 analysis tool and uses a sample of manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The results of this research can explain the miracle phenomenon of the stakeholder approach and upper echelon theory. The research results found that the level of leverage has a positive effect on the quality of manufacturing companies' sustainability disclosures. Meanwhile, the individual characteristics of the President Director have no effect on the quality of manufacturing companies' sustainability disclosures. The research findings provide an insight into the level of well-being from the characteristics of the organization and individual decision makers.
Keywords: Profitability; Leverage; Gender; Age; Sustainability Disclosure